Soil research in Europe with special reference to that in Finland A Review - Sippola, Jouko (MTT, 2005)
The presentation reviews recent European soil research cooperation and areas where Finland has been especially active. The topics include production of European soil map, activities in European Trace Element Network and calculation of soil heavy metal balances. With respect to soil maps after compiling information at a rather rough level, the maps in more detailed scale with related database has been created. In the case of trace element studies, activities have been divided to various areas from general analytical quality control aspects to improve comparability of results to surveys at national and international level. The results of a global investigation revealed the deficiency of zinc to be most common and that of boron in certain countries. More detailed assessment at a country level showed that zinc deficiency may be so serious that no yield is obtained without zinc application. Also, to monitoring of soil pollution development has been paid attention. A way to understand reasons for increased soil pollution has been the making of balance calculations for metals. This serves also in developing control measures. Concerning macronutrients nitrogen has been given much attention because of its high effects on crop yield and environmental pollution. Models have been developed by several groups to understand nitrogen transformations and fate in varying environmental conditions.
Keywords: Ys; soil mapping; soil monitoring; trace elements; nitrogen modelling